(untitled) (Journal of the College of Basic Education, 2026)
This study aims to investigate the effect of Rondo training on developing motor response speed and selected offensive skills among under-17 female basketball players, given the importance of this developmental stage in enhancing the perceptual-motor abilities required for effective performance. The research problem emerged from the researcher’s observation of slow decision-making, weak passing accuracy, and limited dribbling control in tight spaces due to the reliance on traditional training methods that do not simulate real game situations. Therefore, the study sought to examine Rondo training as a method based on speed, pressure, and continuous interaction. The objectives focused on identifying the influence of this training on response speed and basic offensive skills, while the hypotheses assumed significant differences between the pre- and post-tests and between the experimental and control groups. The sample consisted of 12 players from Al-Sulaimaniya Club selected randomly, and the experimental method was used due to its suitability for controlling variables and measuring the effect of the independent factor accurately. The study concluded that adopting Rondo training for under-17 female basketball players contributes to improving several fundamental offensive skills, and recommended integrating Rondo exercises regularly within training programs for this age group due to their effectiveness.